Exhibiting the Extractive: Bitumen in Fort McMurray - Elysia French (Museum & Society)
This article explores how bitumen is curated by the Fort McMurray Oil Sands Discovery Centre and, by extension Suncor’s recent, but no longer operational, ‘Experience the Energy’ tour. In doing so, I seek to examine the visual culture of bitumen as produced from the perspective of industry. The Fort McMurray Oil Sands Discovery Centre is a provincially-funded, industry-sponsored facility operated jointly by Alberta Culture and Tourism and the province’s Historic Sites and Museum Branch. The Centre’s central focus is education and, to enhance this focus, it incorporates entertainment and interactive exhibitions with bitumen throughout, which help to communicate its representation of the histories of the tar sands. I present Suncor’s ‘Experience the Energy’ tour as an extension of the curatorial practices at the Oil Sands Discovery Centre. To do so, I recount my own experience with tar sands tourism in Fort McMurray, framing Suncor’s industrial tourism as a curation of the physical experience of extractive sites, while connecting this to the visual tactics employed at the Centre. In the article, I emphasize how an established visual language, rooted in settler-colonial and extractive-capitalist practices, is adapted to maintain and advance the industrial operations and development of the tar sands. To better understand how visitors come to know bitumen and extraction in these spaces, I consider the sensory as a key component of visual culture to explore how the tar sands industry calls upon visual culture to advance its cause, and suggest that both the tour and the Centre are a kind of multisensory curatorial project—one based on bitumen.